2021
DOI: 10.31314/british.10.2.103-113.2021
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Characterization of the Characters in Short Movie Entitled Ibu

Abstract: Character is someone who appears in the story such as in short stories, novels, dramas, or movies. In this research, the researcher would like to analyze the characterization of the characters in the short movie entitled IBU. The research problems of this research are 1). How is the characterization of the characters? 2). What moral value that we got from the movie?. The purpose of this research is to know the characterization of the characters and to know the moral values that can we get. This research used q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In a different story, some characteristics showing character traits like loyal, depressed, book lover, fighter, stubborn, chivalrous, and nice can also be found. Besides personality traits of the main characters, the investigation of literary work presents characterization related to the theme, either novel or movie (Divyani et al, 2023;Rahmah et al, 2021;Famela, 2011) with different focus of discussions covering feminism (Kusumaningtyas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a different story, some characteristics showing character traits like loyal, depressed, book lover, fighter, stubborn, chivalrous, and nice can also be found. Besides personality traits of the main characters, the investigation of literary work presents characterization related to the theme, either novel or movie (Divyani et al, 2023;Rahmah et al, 2021;Famela, 2011) with different focus of discussions covering feminism (Kusumaningtyas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From this research, the writer found that some of Maleficent's characterization as the main character in this movie, they are good girl, grumpy, trouble maker, guardian angels and also a good witch. The second study is from (Rahmah, Mustofa, & Nisa, 2021) with the title "An Analysis of the Characterization of the Characters in Short Movie Entitled Ibu". This study is discussed about the characterization of the characters and the moral values.…”
Section: Introductionmentioning
confidence: 99%